Looking back : the 1947 Partition of India, 70 years on - Jalil, Rakhshanda; Saint, Tarun K.; Sengupta, Debjani (Hyderabad, Telangana, India : Orient BlackSwan, 2019)
Contributed literary collection from Bengali, Urdu and Hindi.
Includes bibliographical references (pages 330-340) and index.
ENH
Chiefly translated from Bengali, Urdu and Hindi languages
Keywords: Since 1947; Indic literature -- Translations into English; Indic literature; English literature; India -- History -- Partition, 1947.; India -- History -- Partition, 1947 -- Literary collections; India -- History -- 1947-; India -- History -- 1947- -- Literary collections; India; History; Literary collections; Translations